Case Series: ATRX Variants in Four Patients with Metastatic Pheochromocytoma - Cortez, Briana N.; Kuo, Mickey J. M.; Jha, Abhishek; Patel, Mayank; Carrasquillo, Jorge A.; Prodanov, Tamara; Charles, Kailah M.; Talvacchio, Sara; Derkyi, Alberta; Lin, Frank I.; Taïeb, David; Del Rivero, Jaydira; et al. (Frontiers in Endocrinology, 2024)
Few reports have highlighted the rare presence of somatic ATRX variants in clinically aggressive, metastatic pheochromocytoma/paraganglioma (PCC/PGL); however, none have addressed detailed clinical presentation (including biochemistry and imaging) and management of these patients. Here, we address these clinical features and management based on four PCC patients with somatic ATRX variants from our National Institutes of Health PCC/PGL cohort. A total of 192 patients underwent exome sequencing (germline, somatic, or both), and four males were found to have somatic ATRX variants (with additional somatic VHL and FH oncogenic variants in patients 2 and 4, respectively). Per-lesion and per-patient comparisons were performed among functional imaging scans performed at the NIH. Biochemical phenotype and response to systemic treatment were evaluated. This mini-series supports prior studies showing aggressive/metastatic PCC in patients with somatic ATRX variants, as all developed widespread metastatic disease. All four PCC patients presented with noradrenergic biochemical phenotype, and some with significant elevation in 3-methoxytyramine. 18 F-FDOPA PET/CT was found to be the superior functional imaging modality, with 100% lesion detection rate when compared to that of 68 Ga-DOTATATE, 18 F-FDG, 18 F-FDA, and 123 I-MIBG scans. While patients did not respond to chemotherapy or tyrosine kinase inhibitors, they responded to targeted radiotherapy using highspecific-activity 131 I-MIBG (Azedra ® ) or 177 Lu-DOTATATE (Lutathera ® ).